Using the queuing theory in mine haulage. Case of Magistral mining operation - Ortiz Sánchez, Oswaldo (2017)
The study minimizes the cycle waiting time of loading and hauling equipment between loading points of the underground mining operation and unloading points on surface. For this purpose the existing loading and hauling system is first analyzed. Present system consists of four underground loading points and 4 unloading spots on surface. The waiting cost is estimated and then the increment in loading points underground is proved for reducing haulage cost which is a bearing component of the mining cost. By applying queuing techniques the possible reduction in waiting cost is obtained by increasing the number of loading points. The information gathered comes from loading and hauling times measured at site. Evaluated variables were number of loading points vs. waiting time cost of haulers and unit cost of underground ore and waste bins.